Metal oxide-based photocatalysis : fundamentals and prospects for application - Zaleska-Medynska, Adriana, author.; Aleksandra, Pieczyńska. (Amsterdam ; Kidlington, Oxford ; Cambridge, MA : Elsevier, 2018)
Includes bibliographical references and index.